INVESTIGATION ON THE INFLUENCE OF SEAGRASS BED ON FRICTIONAL EFFECT IN COASTAL AREA - Ahmad Rosli, Nur Sakinah (Universiti Teknologi PETRONAS, 2018)
Seagrass plays an important role in affecting the flow regime in the coastal area. However, the mechanism relating the seagrass characteristic and its influence on the hydrodynamics of current is still poorly understood. There is numerous study on relation between seagrass and its influence on the hydrodynamics through experimental work as well as numerical modelling. It is not easy to represent this seagrass inside a numerical model for a coastal study. This give challenge to the modeler in reproducing more reliable model. Experiment studies were carried out to examine the frictional effect of seagrass bed to the velocity of current and wave height. Enhalus acoroides, the native seagrass species of Indo-Pacific coastal waters was modelled inside a wave flume with specific shoot density of 103 shoot/m2. The water depth is varied and tested against wave period ranging from 1.5 s second to 2 s to exhibit nearshore wave condition at Merambong shoal, Johor at which Enhalus acoroides was abundantly found in Malaysia.